Gingerols synergize with anthocyanins to induce antioxidant activity in vitro - Abdurrahim, Amna Emhemed; Mazurak, Vera C.; Chen, Lingyun (Frontiers in Nutrition, 2023)
Oxidative stress caused by free radicals contributes to the pathogenesis of multiple chronic health conditions. Phytochemicals protect against oxidative stress; however, low bioavailability from dietary sources limits their health benefits. This study aimed to assess the effects of anthocyanins and gingerols' combination on the cellular antioxidant response of Caco-2 cells against oxidative stress. A strong synergism was observed for anthocyanin-gingerol (Ac-G) w/w combined ratios of 8:1 and 2:1 (dosages of (1+0.125) and (1+0.5) µg/mL) in the cellular antioxidant activity (CAA) and cytoprotective effects, with synergistic effect indicator (SE) values of 1.41 and 1.61, respectively. The synergism of Ac-G combinations promoted cellular antioxidant defense systems and cytoprotective effects by reducing the induced GPx enzyme activity, protecting SOD enzyme activity, reducing cellular ROS generation, increasing glutathione content, and inhibiting lipid peroxidation. Thus, Ac-G combinations showed potential in supporting the endogenous antioxidant systems to protect cells from oxidation and restore physiological redox status. The Ac-G formulation is a promising healthy option that can be developed into functional foods or nutraceutical products. Furthermore, it could help address the low bioavailability of these phenolics, as higher effects were achieved when combining the same doses.